FORMER CONVICTS RUNNING FOR LEGISLATIVE OFFICE: A REVIEW FROM THE PERSPECTIVE OF FIQH SIYASAH AND SUPREME COURT DECISION NO. 46 P/HUM/2018 - sahliah, sahliah (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
The requirements for the candidacy of former prisoners as legislative members are regulated in Article 240 paragraph 1 of Law Number 7 of 2017 concerning General Elections. This article stipulates that former inmates who have served five years or more can run for office, provided that they announce to the public the legal case that has ensnared them. The research entitled Former Prisoners in the Candidacy of Legislative Members is Reviewed from the Perspective of Fiqh Siyasah and the Supreme Court Decision No. 46 P/Hum/2018 using normative research methods involving a statute approach, conceptual approach, and case study approach. Based on the results of the research, former corruption convicts feel disadvantaged and their rights are limited by the implementation of KPU Regulation Number 20 of 2018 which was ratified by the KPU together with the Minister of Law and Human Rights. Therefore, a number of parties submitted a material review to the Supreme Court to cancel the regulation. The Supreme Court in its decision stated that KPU Regulation Number 20 of 2018 is contrary to Law Number 7 of 2017 which has a higher legal standing, as stipulated in the Supreme Court Decision No. 46 P/HUM/2018.